2008
DOI: 10.1029/2007ja012396
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the origins of the Jovian decimetric emission's variability

Abstract: [1] The long-term variability of the Jovian radiation observed at 13-cm wavelength over 30 years is investigated using a physical model of the radiation belts. The model enables us to quantify the effect of the geometric parameter D E on the synchrotron emission. When a full Jupiter rotation is taken into account in the computations, the variability of the total radio flux with D E is only '1% of that measured. Such a dependence is not detectable. In contrast, radio fluctuations observed at a central meridian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 68 publications
(111 reference statements)
0
24
0
Order By: Relevance
“…The observation of changes in the emission from Jupiter's electron belt has been reported since the early 1970s (e.g., Gérard 1970; Klein et al 1972Klein et al , 1989. Correlations with solar wind on timescales of months to years (e.g., Bolton et al 1989;Galopeau & Gérard 2001;Santos-Costa et al 2008) and solar radio flux on timescales of days to a week (e.g., Miyoshi et al 1999;Tsuchiya et al 2011;Kita et al 2013) have been confirmed since the 1990s. However, the response of the electron belt to the solar wind on short timescales has never been considered until the present work.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The observation of changes in the emission from Jupiter's electron belt has been reported since the early 1970s (e.g., Gérard 1970; Klein et al 1972Klein et al , 1989. Correlations with solar wind on timescales of months to years (e.g., Bolton et al 1989;Galopeau & Gérard 2001;Santos-Costa et al 2008) and solar radio flux on timescales of days to a week (e.g., Miyoshi et al 1999;Tsuchiya et al 2011;Kita et al 2013) have been confirmed since the 1990s. However, the response of the electron belt to the solar wind on short timescales has never been considered until the present work.…”
Section: Discussionmentioning
confidence: 85%
“…Changes in the spatial distribution of the electron belt are supposedly driven by either internal or external parameters (e.g., Bolton et al 1989;Brecht et al 2001;de Pater and Brecht 2001;Horne et al 2008;Santos-Costa et al 2008, 2011Kita et al 2013, and references therein). Determining the exact cause(s) of changes in the radio maps in Fig.…”
Section: Data Analysis Results From Rotation-averaged Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Earth declination as seen from Jupiter, D E , varies slowly over a 11.9‐year cycle between the limit values of −3.3° and +3.3°. The effects of this parameter on Jupiter's decimetric emission had been investigated by carrying out data analysis of single dish and interferometric measurements but also by combining models of the electron radiation belt with synchrotron simulation codes or using a 3D Fourier mapping technique to construct the tridimensional structure of the synchrotron radiation [ de Pater and Klein , 1989; Klein et al , 1989; Hood , 1993; Dulk et al , 1997b, 1999a; Leblanc et al , 1997b; Dunn et al , 2003; Sicard et al , 2004; Kloosterman et al , 2005; Santos‐Costa et al , 2008, and references therein]. Data analyses and modeling works have both led to the conclusion that D E cannot induce drastic changes in the appearance of the 2‐D brightness distribution and distorts efficiently the longitudinal profile of the total flux density over periods of time lasting less than a few months.…”
Section: Origins Of Short‐term Variationsmentioning
confidence: 99%
“…However, until the late 1990s [ Miyoshi et al , 1999; Tsuchiya et al , 2010], short‐term variations non‐related to comet‐like impact could never be clearly related to any particular transient magnetospheric phenomena or solar activity. Intensity variations on broader time‐scales (from months to years) have been also observed since the 1970s [ Gérard , 1970, 1976; Gulkis et al , 1973; Berge , 1974; Klein , 1976; Klein et al , 1972, 1989, 2001; de Pater and Klein , 1989; Bolton , 1990; de Pater and Dunn , 2003; Galopeau and Gérard , 2001] and later linked to solar activity [ Bolton et al , 1989; de Pater , 1994; Galopeau and Gérard , 2001; Santos‐Costa et al , 2008].…”
Section: Introductionmentioning
confidence: 99%